Cytotoxic CD4 T Cells in Antiviral Immunity. (22nd November 2011) - Marshall, Nikki B.; Swain, Susan L.
Abstract : CD4 T cells that acquire cytotoxic phenotype and function have been repeatedly identified in humans, mice, and other species in response to many diverse pathogens. Since CD4 cytotoxic T cells are able to recognize antigenic determinants unique from those recognized by the parallel CD8 cytotoxic T cells, they can potentially contribute additional immune surveillance and direct effector function by lysing infected or malignant cells. Here, we briefly review much of what is known about the generation of cytotoxic CD4 T cells and describe our current understanding of their role in antiviral immunity. Furthering our understanding of the many roles of CD4 T cells during an anti-viral response is important for developing effective vaccine strategies that promote long-lasting protective immunity.